2014
DOI: 10.1063/1.4872328
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plasma radius and profile on the development of self-modulation instability of electron bunches

Abstract: Plasmas available for plasma wakefield accelerator experiments may have longitudinal and transverse density profiles that could affect the outcome of an experiment. This paper investigates the effect of plasmas with finite radius and inhomogeneous transverse density profiles on the wakefield excitation and the self-modulation instability (SMI) development in overdense plasmas. We focus here on the case of an electron bunch. Simulation results show that such plasmas generate larger focusing force for the propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…It was shown that the wakefield amplitude cannot exceed the limit imposed by nonlinear elongation of the wave period [32], and the designed operation regime of the AWAKE experiment is close to this limit [33]. A finite plasma radius or weak radial nonuniformity of the plasma have a small effect on the wave growth, if the radial scale of density variation is much greater than the plasma skin depth [34,35]. As selfmodulating beams are many plasma wavelengths long, motion of plasma ions could come into play and hamper wave excitation, if plasma ions are light [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the wakefield amplitude cannot exceed the limit imposed by nonlinear elongation of the wave period [32], and the designed operation regime of the AWAKE experiment is close to this limit [33]. A finite plasma radius or weak radial nonuniformity of the plasma have a small effect on the wave growth, if the radial scale of density variation is much greater than the plasma skin depth [34,35]. As selfmodulating beams are many plasma wavelengths long, motion of plasma ions could come into play and hamper wave excitation, if plasma ions are light [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…With our choice of plasma radius (r p ), a ±5% variation seems to have no significant effect on the wakefield amplitude. It has been shown that a smaller plasma radius can enhance the wakefield's focusing force and hence the SMI's growth rate by hindering the plasma's shielding response to the charge in the drive bunch [21]. However, this effect only becomes prominent when r p approaches σ rb , which, despite the variations of ±5%, is not the case here.…”
Section: Properties Of the Wakefieldsmentioning
confidence: 65%
“…In sec. IV A the dynamics of the beam into the plasma lenses is then computed by a 2D code written to solve the wakefield equations in the linear regime [32]. Finally, the optimization of the collimator system has been conducted to maximize the driver beam dumping by looking at its fundamental interactions with the collimator walls (predicted by GEANT4, see sec.…”
Section: Plasma Lensesmentioning
confidence: 99%